2006
DOI: 10.1260/174795406777641311
|View full text |Cite
|
Sign up to set email alerts
|

“Put Me in Coach… I'm Better Than You Think I Am!” Coaches' Perceptions of Their Expectations in Youth Sport

Abstract: The purpose of the present study was to examine coaches' perception of high and low expectancy athletes' ability and effort expenditure over one half of a season. An additional aim was to examine the direction of any perceived changes in high and low expectancy athletes. Data were collected from 25 coaches based on interactions with 200 athletes using Darley and Fazio's (1980) Expectancy Confirmation process as a theoretical framework. Coaches reported limited flexibility in their perceptions of high and low e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Regarding skiing, one of the participants suggested that FIS points are able to eradicate RAEs although, in a recent study, RAEs were found in skiing for both males and females (Baker, Janning, Wong, Cobley & Schorer, 2014). In addition, this research supports previous work which highlights that increased opportunities and attention is often given to relatively older athletes because they are better performers (Musch & Grondin, 2001;Wilson, Cushion, & Stephens, 2006). For example, in a recent study with hockey players attending a selection camp, it was found that the players selected for the final team were taller, heavier and the majority of them were born between January to June (Sherar, Baxter-Jones, Faulkner, & Russell, 2007), despite the fact that the coaches were aware that their future potential in terms of physical development were the same.…”
Section: Discussionsupporting
confidence: 76%
“…Regarding skiing, one of the participants suggested that FIS points are able to eradicate RAEs although, in a recent study, RAEs were found in skiing for both males and females (Baker, Janning, Wong, Cobley & Schorer, 2014). In addition, this research supports previous work which highlights that increased opportunities and attention is often given to relatively older athletes because they are better performers (Musch & Grondin, 2001;Wilson, Cushion, & Stephens, 2006). For example, in a recent study with hockey players attending a selection camp, it was found that the players selected for the final team were taller, heavier and the majority of them were born between January to June (Sherar, Baxter-Jones, Faulkner, & Russell, 2007), despite the fact that the coaches were aware that their future potential in terms of physical development were the same.…”
Section: Discussionsupporting
confidence: 76%
“…This, in turn, leads to increased attention and more stimulating support from coaches (Mush and Grondin, 2001). In contrast, those who do not excel receive less attention and less support, both in relation to training and to competitions (Wilson et al, 2006). Consequently, this leads to a loss of motivation, as well as impeded self-efficacy (Thompson et al, 2004).…”
Section: 22mentioning
confidence: 99%
“…Harvey et al 2013;Claxton 1988;Wandzilak et al 1988), competition score line (e.g., Calpe-Gómez, Guzmán and Grijalbo 2013), whether the athlete is characterised by high or low expectations (e.g. Wilson, Cushion, and Stephens 2006;Solomon et al 1998), the skill level of the athlete (e.g. Lacy and Darst 1985;Markland and Martinek 1988), and the aims of the coaching session (e.g.…”
Section: Introductionmentioning
confidence: 99%